Doping prevalence among Danish elite athletes - Elbe, A.-M.; Pitsch, W. (Performance Enhancement & Health, 2018)
The objective of this study was to investigate seasonal and all time doping among Danish elite athletes (N = 771, male = 56.5%) and to investigate gender differences. An online survey was conducted (response rate = 57%) which included biographical information as well as randomized response technique questions about seasonal and all-time doping. Concerning last season prevalence, the maximum doping rate was estimated at 30.6% (95% confidence interval 22.6-35.7) and the rate of honest non-dopers was estimated at 69.4%. For the lifetime prevalence of doping, a rate of at least 3.1% dopers (95% confidence interval 0-8.9) and a maximum of 26% (95% confidence interval 13.4-40.8), with a rate of approximately 74% who can reliably be estimated to have never doped throughout their career was identified. No significant gender differences were found. In conclusion, the doping prevalence among Danish elite athletes is similar to that of Dutch and German elite athletes.